Genetic history of the Koryaks and Evens of the Magadan region based on Y chromosome polymorphism data - B. A. Malyarchuk; M. V. Derenko (Вавиловский журнал генетики и селекции)
In order to clarify the history of gene pool formation of the indigenous populations of the Northern Priokhotye (the northern coast of the Sea of Okhotsk), Y-chromosome polymorphisms were studied in the Koryaks and Evens living in the Magadan region. The results of the study showed that the male gene pool of the Koryaks is represented by haplogroups C-B90-B91, N-B202, and Q-B143, which are also widespread in other peoples of Northeastern Siberia, mainly of Paleo-Asiatic origin. High frequency of haplogroup C-B80, typical of other Tungus-Manchurian peoples, is characteristic of the Evens of the Magadan region. The shared components of the gene pools of the Koryaks and Evens are haplogroups R-M17 and I-P37.2 inherited as a result of admixture with Eastern Europeans (mainly Russians). The high frequency of such Y chromosome haplogroups in the Koryaks (16.7 %) and Evens (37.8 %) is indicative of close interethnic contacts during the last centuries, and most probably especially during the Soviet period. The genetic contribution of the European males’ Y chromosome significantly prevails over that of maternally inherited mitochondrial DNA. The study of the Y chromosome haplogroup diversity has shown that only relatively young phylogenetic branches have been preserved in the Koryak gene pool. The age of the oldest component of the Koryak gene pool (haplogroup C-B90-B91) is estimated to be about 3.8 thousand years, the age of the younger haplogroups Q-B143 and N-B202 is about 2.8 and 2.4 thousand years, respectively. Haplogroups C-B90-B91 and N-B202 are Siberian in origin, and haplogroup Q-B143 was apparently inherited by the ancestors of the Koryaks and other Paleo-Asiatic peoples from the Paleo-Eskimos as a result of their migrations to Northeast Asia from the Americas. The analysis of microsatellite loci for haplogroup Q-B143 in the Eskimos of Greenland, Canada and Alaska as well as in the indigenous peoples of Northeastern Siberia showed a decrease in genetic diversity from east to west, pointing to the direction of distribution of the Paleo-Eskimo genetic component in the circumpolar region of America and Asia. At the same time, the Evens appeared in the Northern Priokhotye much later (in the XVII century) as a result of the expansion of the Tungusic tribes, which is confirmed by the results of the analysis of haplogroup C-B80 polymorphisms.